A systematic review on the impact of climate change on occupational mental health: a focus on vulnerable industries - Tang, Wymann Shao Wen; Ho, Cyrus Su Hui (Social Psychiatry and Psychiatric Epidemiology, 2025)
Aims This systematic review aims to examine how climate change and its related stressors may affect the mental health of workers in industries vulnerable to climate change. The review also seeks to evaluate coping strategies used by affected workers, as well as potential interventions to mitigate and prevent these mental health effects. Method A literature search was conducted in June 2024 in databases such as PUBMED, EMBASE, PsycINFO and Web of Science, using a combination of keywords about climate change, mental health or illness, and vulnerable industries. Results A predominance of accessed literature was related to the agricultural industry, with a minority pertaining to the aquaculture, construction and aviation industries. They suggest an increased vulnerability of workers to mental health-related problems, including increased depression, anxiety, psychological distress and suicidality in response to stressors such as increased temperatures and prolonged drought conditions. Besides socioeconomic effects resulting from reduced productivity, climate-related stressors may contribute to increased uncertainty, isolation, a perceived lack of control, and challenges to their sense of identity. Coping methods varied and influenced outcomes of mental wellbeing, with community wellbeing and social connectedness in the agricultural setting being observed to have beneficial effects on levels of psychological distress. Interventions that promoted mental health literacy, the availability of mental health first aid, social cohesion, and adaptability to climate stressors were deemed helpful. Conclusion Environmental stressors interact with mental health in an intricate manner, exerting influence on biological and socioeconomic aspects of a person’s well-being. In an occupational setting, such stressors may also affect social cohesion and one’s personal sense of identity or self-esteem. Building strong social networks and structures to enable self-efficacy and adaptability towards climate change may be key towards promoting mental health resilience amongst workers in vulnerable industries.